Aromatherapy for the treatment of PONV in children: a pilot RCT. Issue 1 (December 2016) - Kiberd, Mathew; Clarke, Suzanne; Chorney, Jill; d'Eon, Brandon; Wright, Stuart
Abstract Background Postoperative nausea and vomiting (PONV) is one of the most common postoperative complications of general anesthesia in pediatrics. Aromatherapy has been shown to be effective in treating PONV in adults. Given the encouraging results of the adult studies, we planned to determine feasibility of doing a large-scale study in the pediatric population. Methods Our group conducted a pilot randomized controlled trial examining the effect of aromatherapy on post-operative nausea and vomiting in patients 4–16 undergoing ambulatory surgery at a single center. Nausea was defined as a score of 4/10 on the Baxter Retching Faces Scale (BARF scale). A clinically significant reduction was defined as a two-point reduction in Nausea. Post operatively children were administered the BARF scale in 15 min internals until discharge home or until nausea score of 4/10 or greater. Children with nausea were randomized to saline placebo group or aromatherapy QueaseEase™ (Soothing Scents, Inc, Enterprise, AL: blend of ginger, lavender, mint and spearmint). Nausea scores were recorded post intervention. Results A total of 162 subjects were screened for inclusion in the study. Randomization occurred in 41 subjects of which 39 were included in the final analysis. For the primary outcome, 14/18 (78 %) of controls reached primary outcome compared to 19/21 (90 %) in the aromatherapy group (p  = 0.39, Eta 0.175). Other outcomes included use of antiemetic in PACU (control 44 %, aromatherapy 52 %P  = 0.75, Eta 0.08), emesis (Control 11 %, 9 % aromatherapy, P  = 0.87, Eta = 0.03). There was a statistically significant difference in whether subjects continued to use the intervention (control 28 %, aromatherapy 66 %, p -value 0.048, Eta 0.33). Conclusion Aromatherapy had a small non-significant effect size in treating postoperative nausea and vomiting compared with control. A large-scale randomized control trial would not be feasible at our institution and would be of doubtful utility. Trial registration ClinicalTrials.govNCT02663154 .